The treatment of iliotibial band friction syndrome. - Noble, C. A. (1979)
Iliotibial band friction syndrome is a common cause of knee pain in long distance runners. The pain is caused by friction of the iliotibial band over the lateral epicondyle of the femur. Two hundred and twenty one cases were seen in a two year period. Tenderness over the lateral epicondyle associated with pain at 30 degrees of flexion on compressing the iliotibial band against the lateral epicondyle is diagnostic. Conservative treatment consisted of treating the cause, mostly training irregularities and the local inflammation mostly with steroid injections and rest. Nine cases failed to respond to conservative treatment and these were treated by surgical release of the posterior fibres of the iliotibial band.